ANALISIS SILABUS PELAJARAN FIKIH KELAS VII MADRASAH TSANAWIYAH: PERSPEKTIF TUJUAN PENDIDIKAN ISLAM - Samsuddin; Abdul Jabar Idharudin (As-Sulthan Journal of Education, 2025)
This study aims to analyze the syllabus of the Islamic Jurisprudence (Fikih) subject for Grade VII of Madrasah Tsanawiyah (MTs) from the perspective of Islamic educational objectives, which emphasize the formation of a holistic and balanced Muslim personality—spiritually, intellectually, emotionally, and socially. A descriptive qualitative approach was employed using document analysis as the primary method. The main data source is the Grade VII Fikih syllabus published by the Directorate of KSKK Madrasah, Ministry of Religious Affairs of the Republic of Indonesia in 2022. Content analysis techniques were used to identify the representation of Islamic educational values within the structure and content of the curriculum. The findings indicate that the syllabus is strongly aligned with the goals of Islamic education, namely, the development of a complete human being. Through the integration of knowledge and practice, the syllabus plays a strategic role in instilling shar‘ī values—not only in terms of knowledge acquisition but also in religious character formation. Fikih instruction is designed to nurture individual and social piety through strengthened worship practices, internalization of moral values, and development of responsibility and empathy. Therefore, the syllabus is not only relevant within the national curriculum context but also responsive to the need for forming a Muslim generation capable of implementing Islamic teachings comprehensively in real life.